Heparin/Collagen-REDV Modification of Expanded Polytetrafluoroethylene Improves Regional Anti-thrombosis and Reduces Foreign Body Reactions in Local Tissues - Shan, Yaping; Chen, Gang; Shi, Qiqi; Huang, Jiaxi; Mi, Yaping; Zhang, Wenbo; Zhang, Huifeng; Jia, Bing (Frontiers in Bioengineering and Biotechnology, 2022)
Prosthetic implants of expanded polytetrafluoroethylene (ePTFE) in the cardiovascular system have a high failure rate over the long term because of thrombosis and intimal hyperplasia. Although multiple surface modification methods have been applied to improve the anti-thrombotic and in situ endothelialization abilities of ePTFE, none have delivered outstanding results in vivo. Our previous study combined heparin/collagen multilayers and REDV peptides to modify ePTFE, and the in-vitro results showed that modification ePTFE with heparin/collagen-REDV can promote the cytocompatibility and antiplatelet property. This study illustrated the physical change, selective endothelial cells capture ability, and in vivo performance in further. The physical test demonstrated that this modification improved the hydrophilicity, flexibility and strength of ePTFE. A competition experiment of co-cultured endothelial cells and vascular smooth muscle cells verified that the heparin/collagen-REDV modification had high specificity for endothelial cell capture. A rabbit animal model was constructed to evaluate the in vivo performance of modified ePTFE implanted in the right ventricular outflow tract. The results showed that heparin/collagen-REDV modification was safe, promoted endothelialization, and successfully achieved regional anti-thrombosis without influencing body-wide coagulation function. The pathologic manifestations and mRNA expression pattern in tissues in contact with modified ePTFE indicated that this modification method may reduce M2-type macrophage infiltration and the expression of genes related to immune and inflammatory responses. The heparin/collagen-REDV modification may lower the incidence of complications related to ePTFE implantation and has good prospects for clinical use.